TRANSPARANSI PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) PADA MASA PANDEMI COVID-19 DI DESA TOWALIDA KABUPATEN WAJO - Ramdhani, Shinta; Mappamiring, Mappamiring; Yahya, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study uses qualitative and descriptive research types to describe and explain the transparency of the management of village income and expenditure budgets during the covid-19 pandemic. Informant retrieval technique using pourposive sampling with a total of 8 (eight) people. Research data were collected through observation, interviews and documentation, then analyzed using the data reduction stage, data presentation and drawing conclusions.The results of this study indicate that the transparency of budget management and village expenditure revenues during the COVID-19 pandemic in the form of document availability and accessibility, clarity and completeness of information, and openness of the process has been provided properly based on the applicable laws and regulations as a regulatory framework that ensure transparency even though the implementation still needs to be improved.